Variation of Izod Values with Temperature in Timber - Sekhar, A. C.; Sharma, R. S. (Indian Forester, 1956)
Study of variation of Izod values with temperature on standard specimens of seven species has been made and straight line equations by the method of least squares has been suggested for each of the species separately for purely practical purposes. Previous work in the field and the present data have been discussed. Slight increase of Izod values with increase of temperature at moisture content well above the fibre saturation point with a possible critical value between 70Â°C. and 90Â°C. has been observed.